Study on Pre-Weakening Pattern and Behavior of ¼ Scale Steel Structure under Blasting Demolition - Aemlaor, Peerasak; Sriphoeon, Kitsada (วารสารวิชาการ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2020)
Blasting demolition which is the method to raze buildings with small amount of explosive is one of the most efficient methods to take down high rise structures. However, only limited research information is available at the moment while the demand for demolition is rising. Therefore, this study is aims to point out proper patterns of pre-weakening structural steel members and amount of C-4 and also study the behaviour of steel structures under blasting demolition. In the study, firstly several candidate plastic hinge sections are tested and compared to efficiently reduce structural strength in order to minimize the amount of the explosive consumption in the demolition. Then secondly, the appropriate amount of C-4 explosive is determined through blasting test. Finally, a purpose-build ¼ scale steel structure is applied the method. The collapse of the structure is designed using analysis program and actual tests are carried out. The results show that the steel structure can be demolished by C-4 explosive through appropriate pre-weakening pattern, amount of C-4 explosive and structure collapse design.